Reduced Dislocation Density of an InP/GaAs Virtual Substrate Grown by Metalorganic Chemical Vapor Deposition - Tsai, Yu-Li; Wu, Chih-Hung (Coatings (Basel), 2022)
Integrating indium phosphide (InP) material on a gallium arsenide (GaAs) substrate to form an InP/GaAs virtual substrate has been an attractive research subject over the past decade. However, the epitaxial growth of InP on GaAs is challenging due to a large mismatch in the lattice constant and thermal expansion coefficient. This paper describes the successful hetero-epitaxy of InP on a GaAs substrate by metalorganic chemical vapor deposition. The hetero-epitaxy in this study utilized a hybrid growth method involving a thin indium gallium arsenide (InGaAs) linearly graded buffer, two-step InP growth, and a post-annealing process. Transmission electron microscopic observations showed that a traditional two-step InP/GaAs virtual substrate was smooth but had a high threading dislocation density (TDD) of 1.5 × 109 cm−2 near the InP surface. The high TDD value can be reduced to 2.3 × 108 cm−2 by growing the two-step InP on a thin InGaAs linearly graded buffer. The TDD of an InP/GaAs virtual substrate can be further improved to the value of 1.5 × 107 cm−2 by removing the low-temperature InP nucleation layer and carrying out a post-annealing process. A possible reason for the improvement in TDD may relate to a dislocation interaction such as the annihilation of mobile threading dislocations. Room-temperature photoluminescence spectra of InP/GaAs virtual substrates with different TDD values were compared in this study. The optical and micro-structural characterization results suggest that the proposed growth method may be feasible for making good-quality and relatively low-cost InP/GaAs virtual substrates for the integration of optoelectronic devices on them.